TRANSFORMATIVE LEADERSHIP OF ADMINISTRATORS AFFECTING EDUCATIONAL QUALITY OF EDUCATIONAL INSTITUTIONS NAKHON SI THAMMARAT PRIMARY EDUCATIONAL SERVICE AREA OFFICE 3 - Polchai, Supatcha; Chanakul, Benjaporn; Chairueng, Nopparat (Journal of MCU Nakhondhat, 2023)
The purpose of this research were to study the transformational leadership of school administrators. study the quality of education of educational institutions A study of executive transformational leadership that affects the quality of education. and to study the development of transformational leadership of administrators that affects the educational quality of educational institutions. Under the Office of Nakhon Si Thammarat Primary Educational Service Area 3 using a survey research method. The sample group was teachers and personnel. Under the Office of Nakhon Si Thammarat Primary Educational Service Area 3, the sample group was selected by stratified random sampling technique. The group of districts where schools were located was used as a random strata. There were 313 people in total. Research tools were questionnaires, 5-level evaluation scales, data analysis by statistics, percentage, mean, standard deviation. Pearson’s correlation coefficient and multiple regression analysis. The research findings were as follows: under the Office of Nakhon Si Thammarat Primary Educational Service Area, Area 3 overall was at a high level. in creating prestige have the highest average and motivational aspect with the lowest average 2. Educational quality of educational institutions Overall, it was at a high level. Change and development of educational institutions have the highest average and the quality of learners 3. The transformational leadership of school administrators had the lowest average. The aspect of encouraging the use of intelligence inspiring and the creation of prestige affecting the quality of education of educational institutions statistically significant at the .01 level. Manage educational institutions based on the principle of participation from all parties. There are many new thought processes. Focus on the success of work is important and able to solve problems rationally.